Cyclophosphamide induces a significant increase in iron content in the liver and spleen of mice. (July 2020) - Sheng, Y; Chen, Y-J; Qian, Z-M; Zheng, J; Liu, Y
Objective: Oxidative stress is one of the major mechanisms of cyclophosphamide (CPX)-induced toxicities. However, it is unknown how CPX induces oxidative stress. Based on the available information, we speculated that CPX could increase iron content in the tissues and then induce oxidative stress. Method: We tested this hypothesis by investigating the effects of CPX on iron and ferritin contents, expression of transferrin receptor 1 (TfR1), ferroportin 1 (Fpn1), iron regulatory proteins (IRPs), hepcidin, and nuclear factor erythroid 2-related factor-2 (Nrf2) in the liver and spleen, and also on reticulocyte count, immature reticulocyte fraction, and hemoglobin (Hb) in the blood in c57/B6 mouse. Results: We demonstrated that CPX could induce a significant increase in iron contents and ferritin expression in the liver and spleen, notably inhibit erythropoiesis and Hb synthesis and lead to a reduction in iron usage. The reduced expression in TfR1 and Fpn1 is a secondary effect of CPX-induced iron accumulation in the liver and spleen and also partly associated with the suppressed IRP/iron-responsive element system, upregulation of hepcidin, and downregulation of Nrf2. Conclusions: The reduced iron usage is one of the causes for iron overload in the liver and spleen and the increased tissue iron might be one of the mechanisms for CPX to induce oxidative stress and toxicities.